Narcisismo e cultura: a relação entre psicologia individual e psicologia social na obra freudiana - Fernandes, Elisângela Barboza (2007)
This work aims to show how the relationship between social psychology and individual psychology is thought about in Freudian theory. It broaches the issue separating nature and culture, which is dealt with in Freudian discourse as fundamental to the makeup of the subject. Along these lines, we highlight two psychoanalytic concepts that surround the problem: narcissism and identification. The theory of narcissism in its intersubjective dimension provides the basis of examining the opposition between these psychologies and a metaphysiological foundation of social bonding, and therefore, of the very makeup of culture in the Freudian perspective. Beginning with the preliminary analysis of Freud s entry into the discussion of phylogenesis, we go through a discussion of the theory of narcissism through which the death instinct takes the stage. We then discuss this concept in its essential dimension - aggressiveness considering the context of reformulations in the psychic apparatus. Finally, we discuss the conception of the psychoanalytic subject as a potential enemy of civilization , of culture as produced by unconscious and irreconcilable conflicts; and the social and individual psychologies as mutually constituting each other